A Clinical Study On The Effect Of Samangadi Taila Lepa In The Management Of Sadyovrana - Panda, Souman Kumar; Raja, M D P; Pachchinavar, K H; Yakkundi, RC; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2021)
Wound healing is the process of repair that follows injury to the skin and other soft tissues. Following injury, an inflammatory response occurs and the cells below the dermis begin to increase collagen production. Later, the epithelial tissue is regenerated. There are three stages to the process of wound healing: inflammation, proliferation and remodeling. Wound literally means a discontinuity or break in the surface epithelium. It is seen as debilitating and scaring disorder usually seen affecting the human being at any age. Samangadi taila is explained in Sushruta samhita as a Vrana Ropaniya drug for freshly occurring wound. The present clinical study aims to a certain the effect of Samangadi taila lepa in management of Sadyovrana (Vranaropana). This study was conducted within the facilities the patients attending the O.P.D. and I.P.D. of Shalya tantra department of the S.S.R.A.M.C. Hospital, Inchal Belagavi have been selected irrespective of their sex, religion, race, occupation etc. The total 30 patients presenting the features of Sadyovrana were selected randomly treated with a Samangadi taila lepa applied for duration of 7 days. It can be concluded that application of Samangadi taila lepa is significant in the management of Sadyovrana (Vranaropana).